Relasi Pendidikan Islam Dan Tradisi Nyadran: Studi di Kelurahan Kedungwuni Timur - Nora Karima Saffana; Moh. Sugeng Sholehuddin; Muhammad Hufron (https://ejournal.insuriponorogo.ac.id/, 2023)
This research aims to describe the relationship between Islamic education and the Nyadran tradition in Kedungwuni Timur Village, Kedungwuni District, Pekalongan Regency. This research uses descriptive qualitative research. The informants for this research consisted of the Village Head, RT and RW heads and community leaders in East Prawasan Village. Data collection techniques through interviews, observation and documentation. Data analysis in this research uses data condensation, data presentation, and drawing conclusions or data verification. The results of this research are as follows: The relationship between Islamic education and the Nyadran tradition is found in 3 values ​​of Islamic education, namely first, the value of worship. The value of worship contained in the Nyadran Tradition means that people consider this tradition to only aim to worship Allah. Within this tradition are prayers that people do as a means of worship by worshiping Allah SWT. Second, Muamalah Value. The Nyadran tradition is a tradition carried out by the community in order to have direct contact in its implementation. The meaning of Muamalah Values ​​is Islamic community relations with other communities without distinguishing between each other. Third, the value of friendship. In the Nyadran Tradition, the first goal is to connect the ties between siblings so that they do not break. By carrying out this tradition, society is more harmonious and peaceful.